Hambatan Dalam Pelaksanaan Peningkatan Hak Guna Bangunan Menjadi Hak Milik Untuk Rumah Tinggal Yang Dibebani Hak Taggungan - Aldino Pratama; Binov Handitya (Universitas Ngudi Waluyo, 2024)
The implementation of upgrading building use rights which are encumbered by mortgage rights to become property rights is a confirmation of the abolition of the original land rights and the granting of new land rights. By eliminating the original rights to the land, the mortgage rights that burden it are also removed. Therefore, creditors object if debtors want to increase their land rights, because this results in the elimination of the original mortgage rights which serve as collateral for repayment of the debtor's debt. This research was conducted to determine the obstacles in implementing the increase in building use rights over land for residential houses which are burdened with mortgage rights to property rights and the efforts that can be made by the debtor to overcome these obstacles. The research method used in this research is an empirical juridical approach, using analytical descriptive, data collection through primary data and secondary data and the analysis method is qualitative analysis, which draws conclusions deductively. The results of the research obtained by the author are obstacles in implementing the increase in building use rights over land for residential houses which are encumbered with mortgage rights to property rights in Ungaran City, where the creditor objects if the debtor increases the building use rights which have been guaranteed and encumbered with mortgage rights, as a result The law that arises from this increase in rights is that the mortgage right which burdens the building use rights automatically terminates with the deletion of the building use rights which have become property rights. Efforts that can be made by debtors if they want to upgrade their building use rights to ownership rights are to pay off their debts first. Alternatively, the debtor can provide additional collateral other than the power of attorney to impose mortgage rights, which is equal to the original mortgage right, as long as the debtor carries out the process of upgrading the building use rights to ownership rights. Abstrak Pelaksanaan Peningkatan Hak Guna Bangunan yang dibebani oleh Hak Tanggungan menjadi hak milik merupakan penegasan mengenai hapusnya hak atas tanah semula dan pemberian hak atas tanah yang baru. Dengan hapusnya hak atas tanah semula tersebut maka hapus pula hak tanggungan yang membebaninya. Oleh karena itu kreditur merasa keberatan apabila debitur ngin melakukan peningkatan hak atas tanah, karena berakibat hapusnya hak tanggungan semula yang menjadi jaminan dalam pelunasan hutang debitur. Penelitian ini dilakukan untuk mengetahui hambatan dalam pelaksanaan peningkatan hak guna bangunan atas tanah untuk rumah tinggal yang dibebani hak tanggunan menjadi hak milik dan upaya yang dapat dilakukan oleh pihak debitur didalam mengatasi hambatan tersebut. Metode penelitian yang digunakan dalam penelitian ini adalah metode pendekatan yuridis empiris, dengan menggunakan deskriptif analitis, pengumpulan data melalui data primer dan data sekunder serta metode analisis adalah analisis kualitatif, yang pengambilan kesimpulannya secara deduktif. Hasil penelitian yang diperoleh penulis berupa hambatan dalam pelaksanaan peningkatan hak guna bangunan atas tanah untuk rumah tinggal yang dibebani hak tanggungan menjadi hak milik di Kota Ungaran, dimana pihak kreditur keberatan apabila debitur melakukan peningkatan terhadap hak guna bangunan yang telah dijaminkan dan dibebani hak tanggungan, akibat hukum yang timbul atas peningkatan hak tersebut adalah hak tanggungan yang membebani hak guna bangunan gugur dengan sendirinya dengan hapusnya hak guna bangunan yang telah menjadi hak milik. Upaya yang dapat dilakukan oleh debitur apabila ingin melakukan peningkatan hak guna bangunan menjadi hak milik adalah dengan melakukan pelunasan terlebih dahulu atas hutangnya. Alternatif lain debitur dapat memberikan jaminan tambahan selain daripada surat kuasa membebankan hak tanggungan, yang senilai dengan hak tanggungan semula,selama debitur melakukan proses peningkatan hak guna bangunan menjadi hak milik.